1998
DOI: 10.1161/01.str.29.9.1765
|View full text |Cite
|
Sign up to set email alerts
|

Prothrombin Gene G 20210 →A Transition Is a Risk Factor for Cerebral Venous Thrombosis

Abstract: Background and Purpose-It has been recently reported that a G3 A transition at nucleotide position 20210 in the 3Ј-untranslated region of the prothrombin gene is associated with elevated plasma prothrombin levels and an increased risk of deep venous thrombosis. To date, it is unknown whether this polymorphism also represents a risk factor for cerebral venous thrombosis (CVT). Methods-Venous blood samples were collected from 45 patients with CVT and from 354 healthy blood donors as controls. A second control gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
68
1
7

Year Published

2003
2003
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 138 publications
(83 citation statements)
references
References 29 publications
7
68
1
7
Order By: Relevance
“…Interventional therapy with mechanical restoration of flow with clot-buster rheolytic thrombectomy was also recently demonstrated 12,13 . Deficiency of protein C, protein S, antithrombin, and factor V Leiden carrier status or resistance to activated protein C are estimated to account for 25%-35% of all occurrences of venous thrombosis 14,15 . Hormonal contraception is used by more than 100 million women throughout the world.…”
Section: Discussionmentioning
confidence: 99%
“…Interventional therapy with mechanical restoration of flow with clot-buster rheolytic thrombectomy was also recently demonstrated 12,13 . Deficiency of protein C, protein S, antithrombin, and factor V Leiden carrier status or resistance to activated protein C are estimated to account for 25%-35% of all occurrences of venous thrombosis 14,15 . Hormonal contraception is used by more than 100 million women throughout the world.…”
Section: Discussionmentioning
confidence: 99%
“…55,56 A meta-analysis of 9 studies, 38 including 360 CVT patients and 2688 control subjects, reported a pooled OR of CVT of 9.27 (95% CI 5.85 to 14.67) for this mutation, 28 which is stronger than its association with VTE in general.…”
Section: Prothrombin G20210a Mutationmentioning
confidence: 99%
“…Of the 17 studies included, 16 were written in the English language [21][22][23][24]26,[29][30][31]35,[37][38][39]41,43,45,46 and 1 in the Chinese language. 32 All included studies were case-control studies.…”
Section: Study Characteristicsmentioning
confidence: 99%